Walking-on-borderland: Karen Strategies and Tactics of Survival at the Thailand-Burma Border - Boonlue, Winai (Thammasat Review, 2017)
This article is based on ethnographic fieldwork with the Karen at both sides of the Thailand-Burma border. I analyse in this paper the different strategies and tactics of survival in the lives of displaced Karen people. Through my methodology of walking with/to the Karen State in an active participation in their conversation and discussion both in a formal interview and in informal interviews, I have discovered strategies of survival through a struggle at the myth and imagination level and at the level of realities. My analysis reveals the Karen´s experience of a culture of death and their efforts to establish a culture of life despite the adversities of everyday life. In this way, my paper is an anthropological contribution to the current peace-building process in Burma.